Touch-modulated van der Waals heterostructure with self-writing power switch for synaptic simulation. (January 2022) - Gao, Caifang; Nie, Qianfan; Lin, Che-Yi; Huang, Fanming; Wang, Liangjun; Xia, Wei; Wang, Xiang; Hu, Zhigao; Li, Mengjiao; Lu, Hong-Wei; Lai, Ying-Chih; Lin, Yen-Fu; et al.
Abstract: Neuromorphic electronics with two-dimensional van der Waals materials meet the ever-increasing demands of both the semiconductor industry and biological engineering, such as miniaturization, structure flexibility, multifunctionality, and low power consumption. However, the majority of reported electronic devices achieve multifarious memory storage states or synaptic plasticity through regulation of an electrical or an optical signal. Herein, we propose an innovative touch-modulated device based on an indium selenide/hexagonal boron nitride/graphene van der Waals heterostructure coupled with a triboelectric nanogenerator. The device is prepared utilizing a simple copper grid shadow mask instead of the expensive and cumbersome electron beam lithography process, exhibits high mobility of 829 cm 2 V −1 s −1, low voltage, and low power consumption. Nonvolatile memory with self-writing power, durability and multibit data storage is achieved through mechanical modulation without an additional gate-voltage supply. Moreover, by adjusting the distance between the two friction layers, essential synaptic plasticity, including short-term and long-term potentiation/depression and paired-pulse facilitation/depression, are successfully imitated in the device. Most importantly, we achieve ultralow power consumption of 165 aJ in tribotronic synapses owing to the ultra-high mobility of InSe. Our tribotronic synapse with self-writing power has great potential to simulate the low-power-consuming neuromorphic bioelectronic devices with multiple functions and lays the foundation for future advanced neuromorphic systems and artificial intelligence. Graphical Abstract: Touch-modulated van der Waals Heterostructure with Self-writing Power Switch for Synaptic Simulation, is demonstrated by an InSe floating-gate device, coupled with a triboelectric nanogenerator (TENG). We demonstrated a zero-writing-power nonvolatile memory with an on/off ratio of 10 4, excellent repeatability over 100 cycles, and diverse data storage, and the whole system has no additional electrical and optical signal input. When InSe transistor is normally/reversely connected with TENG, by adjusting the distance ( D + / D − ) between the two friction layers of TENG, excitatory/inhibitory plasticity behaviours with low-power consumption 165 aJ successfully simulated. ga1 Highlights: The tribotronic synapses compose of a floating-gate transistor with van der Waals heterostructures integrated with a TENG. The NVM features including diverse date storage, on/off resolution of 10 4 and repeatability over 100 cycles were achieved. The excitatory/inhibitory diverse synaptic plasticity behaviors were successfully imitated. The tribotronic synapse exhibited ultralow energy consumption of 165 aJ superior to other work.